The Effect of Padlet Application Towards Students Writing Skill in The Narrative Text at The Eleven Grade Students of SMAN 12 Pandeglang - Sari, Nani Putpita; Novari, Ari Fajria; Munawaroh, Tatu (Universitas Mathla'ul Anwar Banten, 2024)
Nani Putpita Sari (2024). The Effect of Padlet Application Towards Students Writing Skill in the Narrative Text at the Eleven Grade Students of SMA N 12 Pandeglang in Academic Years 2024/2025. This research paper aims to know whether there is a significant effect of Padlet application towards students' writing skill of Recount text at the Eleven Grade of SMAN 12 Pandeglang - Banten in Academic Year 2024/2025. The research paper used the quantitative approach and quasi-experimental design. The technique in choosing the sample is cluster random sampling; the researcher used XI.3 (35 students) as class experiment and XI.6 (36 students) as class control. In the Collecting data technique, the researcher gives pre-test and post-test. In analyzing the data, From the test results with independent sample t-test obtained t-count = -18.249 with significant 2-tailed = 0.000 < a = 0.05, then Ha is accepted and H0 is rejected. In other words, there is a significant effect of using Padlet towards students' writing skills of narrative text.